An Analysis of the Indonesian National Textbook : English for Senior High School, Book 3 for the third year natural and Social Science Programs - Sorohiti, Maryam (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2005)
In response to the implementation of the 1994 English curriculum in Indonesia, the national textbook English for Senior High School, Book 3 for the Third Year for Social and Natural Science Programs was published in 1997 as a compulsory core textbook used for the third year high school students (18-19 years old). This study investigated the match between the textbook and the revised syllabus of 1994 curriculum in terms of learning objectives, themes, functional skills and learning activities. It analysed the tasks in the textbook using the checklist adapted from Littlejohn's task analysis framework. The findings reveal that the textbook which is organized in 16 themes and consisted of 262 tasks (originally 222 tasks) has the following skill distribution: 146 (55.7%) reading tasks, 3 (1.1%) listening tasks, 66 (25.2%) speaking tasks and 47 (18%) writing tasks. It was also found that the match between the tasks and the learning objective categories recommended by the curriculum is 59.5% which means that in terms of learning objectives, the textbook is fairly relevant to the curriculum. The match between the tasks and the recommended themes is 100% which suggests that in terms of themes, the textbook is relevant to the curriculum. In terms of functional skills, the textbook is not relevant to the curriculum since the match between the tasks and the categories of functional skills in the curriculum is only 7.6%. As for learning activities, the textbook is also considered not relevant to the curriculum as the match between the tasks and the learning activities recommended by the curriculum is only 30%. The results show that the textbook should be replaced with a new one, relevant to the curriculum to include categories that fulfill the recommended learning objectives, themes, functional skills and learning activities.